Stone clearance rate based on stone location in the upper urinary tract using Ho:YAG Laser: A tertiary care hospital-based study - Regmi, Prabodh; Maharjan, Prawesh; Adhikari, Nitesh; Yadav, Santosh Kumar; Singh, Chandresh Kumar (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Upper urinary tract stone disease is a common urological condition with significant morbidity, particularly among young and middle-aged adults. Endourological interventions, notably semirigid or flexible ureterorenoscopy using Ho:YAG with or without ureteral access sheath, offer high stone clearance with minimal invasiveness. However, challenges such as UAS negotiation failure and proximal stone migration can compromise outcomes, especially for upper ureteral stones. This study evaluates patient demographics, procedural outcomes, complications, and stone clearance rates following uretero-renoscopic laser lithotripsy.Materials and Methods: This cross-sectional study was conducted at Department of Surgery, Devdaha Medical College and Research Institute from 1st August 2024 to 31st July 2025, following ethical approval. Consecutive patients undergoing low-power Ho:YAG laser lithotripsy for upper urinary tract stones, meeting inclusion and exclusion criteria, were enrolled. Data were analyzed using Excel and SPSS version 20.Results: Forty-nine patients were included; 67.3% were aged 20–39 years, with a nearly balanced sex distribution (females 53.1%, males 46.9%; p = 0.775). Stones were almost equally distributed between right (51.0%) and left (49.0%) sides (p = 1.000). UAS placement failed in 15.4% of procedures. Semi-rigid URS achieved complete removal of upper ureteral stones in 62.5%, while 37.5% migrated proximally. Postoperative fever occurred in 8.1% of patients, and blood transfusion wasn’t needed. Overall stone clearance was 95.4%Conclusions: Upper urinary tract stones predominantly affect younger adults, with no significant sex or laterality predilection. The uretero-renoscopic lithotripsy using Ho:YAG laser demonstrates excellent stone clearance and low complication rates, reinforcing its role as a safe, and effective for upper urinary tract stone management.